Family planning: its practice and determinants among eligible couples in an urban slum of Tripura - Bhattacharjya, Himadri; Reang, Taranga (International Journal of Research in Medical Sciences, 2017)
Background: Contraceptive use in India is poor so this study was designed to detect the prevalence of contraceptive use and its determinants among eligible couples in an urban slum of Tripura. Methods: Community based cross-sectional study, conducted in the urban field practice area of Agartala Government Medical College during 15th June 2010 to 14th August 2010 among 180 eligible couples chosen by systematic random sampling. Descriptive statistics and chi-square test were used. Results: Majority were Hindu from nuclear families. 56.7% wives and 62.8% husbands studied up to secondary level. Prevalence of contraceptive use was 43.9% and 88.9% of the study couples were aware about family planning. Tubal ligation was the most adopted and condom was the least practiced method. Decision regarding family planning was mostly made by the husband and wife jointly. Public health facilities were the main source of family planning materials and most of the study couples opined family planning as essential. Commonest reason for not practicing family planning was the desire for a son and the rest were fear of adverse effects and some non-specific reasons. The affect of caste, religion, occupation, education etc. was insignificant in determining the practice of family planning. Conclusions:Despite a high rate of desire to limit family size, less than half of the couples were currently using contraception. It was mostly due to desire for more male babies. Hence behaviour change communication for eliminating preference for male babies and measures favouring girl children may promote couple protection in this community.